Improving performance of Tenebrio molitor: The effects of media composition and thickness on chitin content, protein quality, and fat digestibility - Brilyant, Chessy; Nuraini, Nuraini; Fajrona, Kadran; Rahmadhani Bakhri, Sarah; Fadli, Muhammad (Jurnal Ilmu Peternakan Terapan, 2026)
This study investigated the potential of Tenebrio molitor (mealworm) larvae as a sustainable protein source for animal feed. The effects of growth media composition and thickness on performance, chitin content, protein quality, and fat digestibility were analyzed. The research used an experimental Completely Randomised Design in a 3x3 factorial arrangement with three replications to examine the following factor A media compositions: A1 (50% Commercial ration + 50% Tofu dregs), A2 (50% Commercial ration + 50% Palm kernel meal), and A3 (50% Commercial ration + 50% Rice bran) and Factor B media thicknesses: B1 (1 cm), B2 (2.5 cm), and B3 (4 cm). The parameters evaluated were performance metrics, chitin concentrations, crude protein, nitrogen retention, and fat digestibility. Variance analysis demonstrated a highly significant interaction between composition and thickness across all parameters (P<0.01). The ideal formulation was a combination of commercial feed combined and tofu dregs at a thickness of 4 cm producing the following of exceptional outcomes: consumption of 291.40 g per 1000 larvae, body weight gain of 80.79 g per 1000 larvae, media production of 90.13 g per 500 g, chitin content of 14.34%, crude protein of 55.64%, nitrogen retention of 77.74%, and digestibility of crude fat of 89.28%. Therefore, it can be concluded that the combination of 50% commercial feed and 50% tofu waste with a medium thickness of 4 cm was the most effective treatment for improving the performance, chitin content, protein quality, nitrogen retention, and fat digestibility of Tenebrio molitor larvae.